To the Edge : Legality, Legitimacy, and the Responses to the 2008 Financial Crisis - Wallach, Philip A. (Book collections on Project MUSE., 2015)
"In To The Edge: Legality, Legitimacy, and the Responses to the 2008 Financial Crisis, Philip Wallach chronicles and examines the legal and political controversies surrounding the government's responses to the recent financial crisis. The economic devastation left behind is well-known, but some allege that even more lasting harm was inflicted on America's rule of law tradition and government legitimacy by the ambitious attempts to limit the fallout. In probing these claims, Wallach offers a searching inquiry into the meaning of the rule of law during crises."--Provided by publisher.